The Effect of Sodium Restricted Diet on Plasma Visfatin Levels in Hypertensive Patients with Visceral Obesity - Sylwia Rotkegel; Jerzy Chudek; Urszula Spiechowicz-Zaton; Rafal Ficek; Marcin Adamczak; Andrzej Wiecek (Karger Publishers, 2013)
Aim/Background: Experimental and clinical studies revealed contradictory data concerning the influence of renin-angiotensin-aldosterone (RAA) system activation on visfatin release. The aim of the present study was the assessment of the effect of dietary sodium restriction with RAA system activation on visfatin level in hypertensive and normotensive patients with visceral obesity. Methods: The study included 24 hypertensive patients with visceral obesity (12 women) and 22 normotensive subjects with visceral obesity (11 women) constituting the control group. Plasma renin activity, plasma insulin, aldosterone and visfatin levels were determined twice, on normal-salt diet after 6-8 h in recumbent position and the second time after 3 days of dietary sodium restriction and upright position for 2 h. Dietary compliance was controlled by 24 h natriuresis measurement. Results: Hypertensive patients had significantly higher plasma visfatin level than the control group [11.0 (8.5-13.5) vs. 6.8 (6.0-7.6) ng/ml, p=0.003]. Dietary sodium restriction and upright position caused significant increase in PRA and plasma aldosterone level in both groups. While, plasma visfatin level remained unaffected. In the combined group plasma visfatin levels correlated with BMI (r=0.398), waist circumference (r=0.391), glucose (r=0.328), insulin (r=0.663), HOMA-IR (r=0.698), triglycerides (r=0.500) and CRP (r=0.546) but not with percentage of fat mass, percentage of trunk fat, and blood pressure values. Conclusions: 1) Increased plasma visfatin concentration may play a significant role in the pathogenesis of hypertension in patients with visceral obesity. 2) RAA system activation by dietary sodium restriction and upright position has no effect on plasma visfatin levels in subjects with visceral obesity.